Through the Back-Door: How Australia and Canada Use Working Holiday Programs to Fulfill Demands for Migrant Work Via Cultural Exchange - Vosko, Leah F. (Journal of Industrial Relations, 2023)
In Australia and Canada, working holidaymaking is rationalized on the basis of encouraging cultural exchange among youth. Yet, in both countries, there is mounting evidence that working holiday programs are operating as back-door migrant work programs to help fill demands for labor in occupations and industries characterized by precarious jobs undesirable to locals. As scholarship on working holidaymakers’ labor market participation is more developed in Australia than in Canada, and administrative data available are also more extensive therein, this article sheds new light on the Canadian case vis-à-vis the Australian example. In exploring regulatory strategies adopted by these two settler states and their effects, comparative analysis of administrative data and historical and contemporary immigration and labor and employment laws and policies reveals how nationally specific program design can foster similar ends: precariousness among participants in the industries in which working holidaymakers are concentrated, including agriculture, tourism, and accommodation and food services. It also shows that stratification between working holidaymakers more closely approximating the image of the “cultural sojourner” and those who are effectively migrating for work purposes takes shape principally along the lines of source country in both countries.
https://www.researchgate.net/publication/365248611_Through_the_back-door_How_Australia_and_Canada_use_working_holiday_programs_to_fulfill_demands_for_migrant_work_via_cultural_exchange

Transnational Employment Strain in a Global Health Pandemic: Migrant Farmworkers in Canada - Vosko, Leah F.; Basok, Tanya; Spring, Cynthia (Palgrave Macmillan, 2023)
The 2020-22 COVID-19 pandemic reinforced inequalities between the global North and South, amplifying pre-existing disparities between migrant and citizen/permanent resident workers in receiving and sending states worldwide. In contexts such as Canada, it also underscored that many workers in occupations and sectors deemed “essential” enough to be exempt from stay-at-home orders and other public safety measures are migrants, a sizeable number of whom sustain Canada’s food supply through their work in its agricultural industry. This book explores the dynamics behind the pandemic’s deleterious outcomes for this vital group of workers, highlighting migrant farmworkers importance to the Canadian economy, society, and the world of work alongside the conditions they endured before and during the global health pandemic through policy and media analysis and open-ended interviews with workers enrolled in two streams of Canada’s Temporary Foreign Worker Program (TFWP) as well as migrants without legal status employed in agriculture located in Ontario and Quebec. Advancing the notion of transnational employment strain, the authors derive insight from the employment strain model, a framework for understanding risks to the physical and psychological well-being of workers, and expand it to account for migrants’ relationships across transnational space. –Publisher's description
https://www.researchgate.net/publication/366779493_Transnational_Employment_Strain_in_a_Global_Health_Pandemic_Migrant_Farmworkers_in_Canada OCLC: 1342620501
Keywords: COVID-19 Pandemic; 2020-2023 Economic aspects Canada; Canada; Economics; Influence (Literary; artistic; etc.); Migrant agricultural laborers; Migrant agricultural laborers Canada; Migrant agricultural laborers Government policy; Migrant agricultural laborers Government policy Canada; Pandémie de COVID-19; 2020-2023 Aspect économique Canada; Since 2020; Travailleurs agricoles migrants Canada; Travailleurs agricoles migrants Politique gouvernementale Canada

“Vulnerable Workers” and Third Way Governance: Shifting Subjects of Regulation in Ontario’s Employment Standard Enforcement Regime - Hall, Alan; Grundy, John; Vosko, Leah F.; Hall, Rebecca (Journal of Law and Political Economy, 2023)
This article traces the definition and treatment of “vulnerable workers” within the province of Ontario’s regulation of employment standards over a fourteen-year period. An examination of the government’s discourse and its enforcement and legislative history reveals significant shifts and inconsistencies between the government’s claims and its enforcement practices. These shifts and inconsistencies are understood within a political economic analysis of “Third Way” employment policies, competing liberal ideologies, shifting political-economic conditions and institutional legacies. The analysis contributes to a cross-national literature exploring the inadequacies of employment standards enforcement in liberal market economies while at the same time identifying opportunities for change within the different “varieties of liberalism” exhibited within Third Way regimes.

The Origins and Application of the "Core of Indianness" in Indigenous Labour Relations: Returning to Four B Manufacturing v. United Garment Workers of America - King, Adam D. K.; Lyubchenko, Olena; Vosko, Leah F.; Noack, Andrea M.; Coburn, Veldon; Hall, Rebecca J. (Labour / Le Travail, 2023)
This article examines the history of, and legal precedent set by, Four B Manufacturing v. United Garment Workers of America, a 1980 Supreme Court of Canada case involving an Indigenous-owned manufacturing firm that resisted the efforts of its Indigenous and non-Indigenous workers to form a union on the Tyendinaga Mohawk Territory, a reserve in southeastern Ontario. The employer, Four B, contested the jurisdiction of the Ontario Labour Relations Board and argued, unsuccessfully, that as an "Indian enterprise," its own operations were a matter of federal jurisdiction. We return to the case of Four B for three interrelated reasons. First, we argue that Four B remains relevant because of the ways that the political economy of settler-colonial Canada continues to structure Indigenous enterprises, labour, and employment as ongoing sites of tension. Second, as the inaugural case dealing with the "core of Indianness" – a contested legal concept used by the courts to determine federal jurisdiction over Indigenous labour – this case both set the legal precedent and shaped the subsequent political terrain of Indigenous labour relations. Third, the issues addressed in Four B contextualize recent jurisdictional struggles over Indigenous enterprises, labour, and employment in what we term the "Indigenous public sector" – namely, health care, social services, and First Nations government administration. The article reviews the case history of Four B, setting this against the backdrop of deindustrialization in southeastern Ontario during the period, before tracing how the case influenced the juridical and political landscape of Indigenous labour relations. We close by considering the potential tensions between Indigenous self-determination and the exercise of collective bargaining rights by Indigenous workers.
Keywords: "core of Indianness"; Indigenous labour relations; colonialisme de peuplement; juridiction; jurisdiction; public-sector unionism; relations du travail autochtones; settler colonialism; syndicalisme dans le secteur public; « cœur de l'Indianité »